The Use of Massage Therapy as a Nonpharmacological Approach to Relieve Postlaparoscopic Shoulder Pain: a Pediatric Case Report - Zerkle, Deborah (Int J Ther Massage Bodywork, 2020)
INTRODUCTION: Postlaparoscopic shoulder pain (PLSP) has been well documented to effect patients following an abdominal or thoracic laparoscopic surgery. PLSP is characterized by referred pain that can occur both unilaterally or bilaterally, and is typically caused by phrenic nerve irritation. Current literature has focused on pharmacological treatment; however, there is limited evidence for the use of nonpharmacological management of PLSP in the pediatric population. CASE DESCRIPTION: This retrospective case report study explores the use of a single-session massage therapy treatment for a 17-year-old patient with PLSP following laparoscopic abdominal surgery. INTERVENTION AND RESULTS: Therapy intervention included a 25 min Swedish massage involving the effected shoulder with an emphasis on passive touch to the shoulder and at the level of the diaphragm. Pain was assessed using the Visual Analog Scale (VAS) pre- and postintervention. Following therapy the patient reported 0/10 pain. CONCLUSION: This case report provides evidence for the use of massage therapy treatment as a noninvasive, nonpharmacological approach to reducing or eliminating PLSP in a pediatric patient.